FATHER ENGAGEMENT PROGRAM FOR STUNTING PREVENTION: A COMMUNITY SERVICE ACTIVITY IN TALANG BANJAR PRIMARY HEALTH CENTER, JAMBI CITY - Sonia, Gina; Kusdiyah, Erny; Tri Hardiningsih, Denok; Puspasari, Anggelia; Nuriyah, Nuriyah; Fitri, Amelia Dwi; Herlambang, Herlambang (Universitas Jambi, 2026)
Background: Stunting remains a significant health problem in Jambi City, with Talang Banjar Primary Health Center recording the highest number of cases (113 children) in 2024. Fathers’ involvement in stunting prevention is often overlooked despite their strategic role in family decision-making. Objective: This community service activity aimed to implement a father engagement program to increase fathers’ awareness and participation in stunting prevention in the working area of Talang Banjar Primary Health Center. Methods: The activity was conducted through a one-day workshop attended by 40 fathers of children aged 0-59 months. The program included an interactive lecture on stunting prevention, a nutritional label reading practice session, and a group discussion on fathers’ roles in family nutrition. Results: The workshop was attended by 40 fathers from for villages in the working area of Talang Banjar Primary Health Center. Participants showed high enthusiasm during the interactive lecture and practical sessions. Based on observations and discussions, fathers expressed increased awareness of the importance of their involvement in stunting prevention. Several challenges were identified, including time constraints and economic factors, which need to be addressed in future programs. Conclusions: The father engagement program through a one-day workshop successfully engaged fathers and increased their awareness of stunting prevention. This community service activity demonstrates he potential of rather-focused interventions to support stunting reduction efforts in Jambi City. Recommendations for future programs include integrating father engagement into routine primary health center activities and conducting follow-up evaluations. Keywords: father engagement; stunting prevention; community service; workshop